An 114 Hz–12 MHz digitally controlled low‐pass filter for biomedical and wireless applications. Issue 5 (8th May 2018) - Elamien, Mohamed B.; Mahmoud, Soliman A.
Abstract : This study presents a wide tunable Gm‐C low‐pass filter for biomedical and wireless applications. The proposed filter was designed using the standard 90 nm complementary metal–oxide–semiconductor technology operating with a balanced supply voltage of 1.2 V. Modified linearisation techniques are used to improve the linearity of the digital programmable operational transconductance amplifiers (DPOTAs) which are used in the filter design. The proposed filter consists of three parallel fourth‐order Butterworth sections. Each section is designed and optimised to target a specific band of frequencies. The operation of selecting between the different sections is free of any physical switches. Turning off the unwanted sections is utilised by setting the control bits of the corresponding DPOTAs to zeros. The performance of the proposed filter and DPOTAs is validated through simulation results. The third‐order harmonic distortion of the DPOTA remains below −60 dB up to 0.5 V differential input voltage. The simulation results show that the digitally tunable cutoff frequency of the proposed low‐pass filter is widely varied in the range of 114 Hz–12 MHz. The proposed filter achieves IIP3 of 28 dBm.